Research status and prospects of acupuncture for autism spectrum disorders - Li, Xiang; Li, Ji-Cheng; Lu, Qi-Qi; Zhang, Fan; Zhang, Shan-Qiang (Frontiers in Psychiatry, 2023)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder and has a predilection for children. It's symptoms, such as lifelong social communication deficits and repetitive sensory-motor behaviors put a huge burden on the patient's family and society. Currently, there is no cure for ASD, and some medications that can improve its symptoms are often accompanied by adverse effects. Among many complementary and alternative medicine (CAM) therapies, acupuncture has shown promising application potential, but after years of practice, it has not been recognized as the preferred CAM therapy for ASD. Therefore, we analyzed and discussed the clinical study reports of acupuncture in the treatment of ASD in the past 15 years from the aspects of study subjects, group setting, intervention modalities, acupoint selection, outcome evaluation and safety. The data accumulated at present showed that acupuncture is beneficial to ASD, but it is not enough to support its clinical effectiveness. Based on a comprehensive analysis, we believed that following the Standards for Reporting Interventions in Clinical Trials of Acupuncture (STRICTA) and Consolidated Standards of Reporting Trials (CONSORT), screening the optimal combination of acupoints through scientific study design, and performing the related functional experiments may be the effective ways to promote acupuncture as the preferred CAM therapy for ASD in the future. The significance of this review is to provide a reference for researchers to carry out high-quality clinical trials of acupuncture in the treatment of ASD from the perspective of the combination of modern medicine and traditional Chinese medicine.